Hepatite B (VHB) e Delta (VHD) em cinco municípios do Estado Maranhão: prevalência e fatores associados - NUNES, Jomar Diogo Costa (2018)
Introduction. Hepatitis B Virus (HBV) infection can lead to chronic disease. Hepatitis Delta virus (HDV) coinfection may favor an increased risk for liver cirrhosis and hepatocellular carcinoma (HCC) in HBV carriers. HBV infected individuals may present detectable HBV DNA with absence of hepatitis B surface antigen (HBsAg). HBV and HDV infections prevalence rates are heterogeneous in Brazil. The aim of this study was to estimate the prevalence of HBV and HDV infections located in the state of Maranhão in Brazil (Axixá, Morros, Icatu, Humberto de Campos and Urbano Santos). Methods. A total of 3.856 to 4,000 individuals participated of this study. Sample size was obtained by considering a prevalence of 0.5% of HBsAg (according to previous national survey), absolute error of 0.3% and 95% confidence interval. Individuals should be age 1 or older to participate in this study. Questionnaires were applied to identify sociodemographic characteristics and transmission risk factors. Samples of blood were collected and serologies were performed for HBsAg, antiHBc, anti-HBs and anti-HDV markers by enzyme-linked immunosorbent assay (ELISA). Results. A total of 3.984 individuals were screened for HBsAg serological markers. The prevalence of HBsAg was 2.30%. Anti-HBc marker was found in 38.47% of samples, 13.95% and 20.10% presented isolated anti-HBc and anti-HBs respectively. Considering the 3,984 samples, anti-HDV was found in 0.35% individuals (among the 92 HBV carriers, eight presented the anti-HDV marker, corresponding to 8.6%). Among the 561 participants with anti-HBc alone, 223 (39.75%) Conclusion. The prevalence of HBV in the region was considered to be intermediate (more than 2% of carriers). Among those carriers, 8% tested positive for anti-HDV. Thus, prevention measures should be implemented to prevent Infection by these viruses and progression to liver cirrhosis and HCC.